2019
DOI: 10.1080/15397734.2019.1674664
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon nanotubes on thermal expansion coefficient and thermal buckling of polymer composite plates: experimental and numerical investigations

Abstract: The first aim of this paper is to experimentally explore the effect of multi-walled carbon nanotubes (MWCNTs) on the coefficient of thermal expansion (CTE) of epoxy-based composites. Focusing on the obtained experimental data, two important conclusions can be drawn. 1) Though the CTE of carbon nanotubes (CNTs) is lower than that of neat epoxy, using more CNT does not necessarily decrease the CTE of epoxy polymer. 2) The optimum weight percent of CNT is 0.3 which can reduce the CTE of epoxy up to 33%. As the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…k th is thermal conductivity matrix. When the material is isotropic, the matrix can be expressed as Equation (8).…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…k th is thermal conductivity matrix. When the material is isotropic, the matrix can be expressed as Equation (8).…”
Section: Thermal Analysismentioning
confidence: 99%
“…Adding the T700/M-epoxy increases composite mechanical strength. Kamarian et al added MWCNTs to the epoxy and observed the effects on the coefficient of the composite thermal expansion [8]. Adding MWCNTs to the epoxy decreased the coefficient of the composite thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…nanostructured materials have attained much research interest due to its promising distinctive features such as large specific surface area, excellent organic adsorption capability, and good mechanical strength. [1][2][3][4][5][6][7][8][9][10][11] Nanomaterials include nanoparticles, [12][13][14] nanowires, 15 nanotubes, [16][17][18][19][20] and nanofibers. [21][22][23] Among these structures, nanofibers are the most diversified one-dimensional (1D) nanomaterials for the extensive research and commercial application due to its multifunctional and multi-tuned microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials include nanoparticles, 12–14 nanowires, 15 nanotubes, 16–20 and nanofibers 21–23 . Among these structures, nanofibers are the most diversified one‐dimensional (1D) nanomaterials for the extensive research and commercial application due to its multi‐functional and multi‐tuned microstructures 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–12 ] These approaches show superior performance in coping with this problem than any other approach. Furthermore, several works studied the heat conduction in nanocomposites, [ 13–17 ] and nanostructures theoretically [ 18–21 ] and experimentally. [ 22–24 ]…”
Section: Introductionmentioning
confidence: 99%